2012
DOI: 10.1016/j.pmrj.2012.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes of Women With Physical Disabilities: A Matched Cohort Study

Abstract: Our study describes a cohort of women who had moderate-to-severe physical disabilities who historically have been discouraged from pregnancy. Women with physical disabilities experienced higher rates of preterm deliveries, low birthweight infants, and pregnancy complications. The pregnancy complications in most cases were not severe and were readily managed. Although it was common to experience functional changes during pregnancy, these changes had largely resolved by 6 weeks postpartum. Larger observational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 23 publications
3
85
0
1
Order By: Relevance
“…Physical disabilities can cause educational, informational, physical, and financial obstacles during the women's perinatal period that can lead to less perinatal care experience, and may have an influence on health outcomes [17]. There are few studies that have shown that most disabled women will have good pregnancy outcomes; however, some data indicates that complications may be more prevalent among women with physical disabilities, according to the nature and severity of the underlying condition.…”
Section: Discussionmentioning
confidence: 99%
“…Physical disabilities can cause educational, informational, physical, and financial obstacles during the women's perinatal period that can lead to less perinatal care experience, and may have an influence on health outcomes [17]. There are few studies that have shown that most disabled women will have good pregnancy outcomes; however, some data indicates that complications may be more prevalent among women with physical disabilities, according to the nature and severity of the underlying condition.…”
Section: Discussionmentioning
confidence: 99%
“…Early initiation of epidural anesthesia with continuation through the first 24 hours postpartum is recommended to avoid recurrent episodes of AD. 40,43,44 Some postpartum women with SCI will also experience AD during initiation of breastfeeding and will need assistance and monitoring during feeding for the first few days. 22,40,43 However, this is not a reason to discourage the desire to breastfeed.…”
Section: Autonomic Dysreflexiamentioning
confidence: 99%
“…43 In a cohort study, the investigators found that the women who became pregnant after SCI were twice as likely to experience preterm labor and birth as those who became pregnant before having SCI. 43 In addition, women who became pregnant after SCI were very likely to have infants with lowbirth-weight.…”
Section: Preterm Labor and Birthmentioning
confidence: 99%
See 2 more Smart Citations